2015
DOI: 10.1186/s40064-015-1036-1
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio may be associated with the outcome in patients with prostate cancer

Abstract: PurposeEvidences have shown that neutrophil-to-lymphocyte ratio (NLR) has a prognostic value in patients with cancer. We wanted to test the prognostic significance of NLR in prostatic cancer of patients who are candidate to radical prostatectomy.MethodsWe have considered 731 patients. Complete demographic data including age, tumor stage, Gleason score, complete blood count and serum biochemical profile were collected. Pre-treatment percentage of neutrophils and NLR were considered, and correlated with patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 20 publications
2
53
1
1
Order By: Relevance
“…In addition, there were only a few studies that investigated the importance of preoperative NLR in prediction of BCR after RP in localized prostate cancer. 15,16 Minardi et al 15 tested the prognostic significance of NLR in the prostate cancer of patients who were candidates for a RP. In that study, they reported that patients with a NLR of 43 had a higher incidence of recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there were only a few studies that investigated the importance of preoperative NLR in prediction of BCR after RP in localized prostate cancer. 15,16 Minardi et al 15 tested the prognostic significance of NLR in the prostate cancer of patients who were candidates for a RP. In that study, they reported that patients with a NLR of 43 had a higher incidence of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…8,14 In addition, there were only a few studies that investigated the importance of preoperative NLR in prediction of biochemical recurrence (BCR) after radical prostatectomy (RP) in localized prostate cancer. 15,16 However, the prognostic significance of NLR in terms of survival in patients who have undergone RP for prostate cancer has never been previously evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…A summary of 15 recent studies investigating the prognostic role of NLR in PC is shown in Table . Six studies investigated the prognostic value of NLR in patients who underwent radical prostatectomy for PC; five studies evaluated the preoperative value, and the remaining studies evaluated postoperative values.…”
Section: Differential Blood Cell Markersmentioning
confidence: 99%
“…A summary of 15 recent studies investigating the prognostic role of NLR in PC is shown in Table 12. 76,88,[129][130][131][132][133][134][135][136][137][138][139][140][141] Six studies investigated the prognostic value of NLR in patients who underwent radical prostatectomy for PC; five studies evaluated the preoperative value, and the remaining studies evaluated postoperative values. The outcomes of those studies included survival (BCRFS, CSS and OS), as well as pathological results.…”
Section: Nlr In Pcmentioning
confidence: 99%
“…A few studies reported that an elevated NLR has prognostic value after radical prostatectomy (RP) for localized PC [1618]. However, most of these focused on the prognostic value of NLR in the preoperative setting; no study has assessed the association between postoperative NLR and prognosis after RP for PC.…”
Section: Introductionmentioning
confidence: 99%